E-084 Reconstructive and deconstructive endovascular treatment outcomes of carotid blowout syndrome. (22nd July 2019) - Sweidan, A; Schnure, A; Yuki, I; Fujitani, R; Suzuki, S
Abstract : Introduction: Carotid blowout syndrome (CBS) is a rare but dreaded complication of head and neck cancer with high mortality. Management of CBS requires a multidisciplinary approach; nevertheless, endovascular therapy remains the cornerstone in rendering hemostasis. Literature routinely describes successful hemostasis with either deconstructive (artery take down) or reconstructive (stenting or bypass) approach. Previous retrospective analysis suggests that outcomes are predicted by clinical severity at presentation, not treatment type. Methods: Single-center, retrospective case review of endovascular treatment of CBS and outcome at University of California, Irvine. Results: Five cases of CBS were identified between 2012 to 2017. All patients were head and neck cancer treated with radiation. Of the five cases, one case failed to identify the source of bleeding which required open surgical ligation. In the remaining four patients, three achieved hemostasis with reconstruction, while the fourth was treated with deconstruction. In one of the three cases, reconstructive over deconstructive technique was chosen because the patient had bilateral lesions and previous embolization at the bleeding site failed to maintain hemostasis. All four patients were discharged from the hospital without any further complications related to the procedure achieving hemostasis. Perioperative mortality, stroke and infection rate was not identified. In the case of surgical ligation, the patient developed minor local site infection which was treated with antibiotics successfully. Endovascular approaches permit evaluation of collateral circulation in situations where target artery warrants take down. Therefore, concurrent cerebral angiogram with endovascular therapy by way of stenting or sacrificing the target artery with embolic materials has become the alternative in otherwise inoperable condition as an emergent standard of care. The figure shows an illustrative case of CBS with massive contrast extravasation (A), which was treated with a balloon mounted covered stent (B) due to bilateral lesions, and complete hemostasis was achieved (C). Conclusion: In our retrospective study we demonstrate continued endovascular therapy as a means of treatment for CBS to achieve emergent hemostasis. As previous literature describes successful hemostasis with either deconstructive or reconstructive technique; herein we describe four cases that required endovascular intervention with successful emergent hemostasis. Disclosures: A. Sweidan: None. A. Schnure: None. I. Yuki: None. R. Fujitani: None. S. Suzuki: None.